Chemical investigation and antimicrobial properties of mastic water and its major constituents - Paraschos, S.a; Magiatis, P.a; Gousia, P.b; Economou, V.b; Sakkas, H.b; Papadopoulou, C.b; Skaltsounis, A.-L.a (Food Chemistry, 2011)
Mastic water is a commercial flavouring obtained during the steam distillation of mastic resin (the resin of Pistacia lentiscus var. chia) for the production of mastic oil. The mastic water extracts were analysed by GC-MS. The major compounds identified were verbenone, α-terpineol, linalool and trans-pinocarveol. Overall the composition was found to be very different from that of mastic oil. Additional GC-MS revealed the enantiomeric ratio of the chiral constituents of mastic water. The antimicrobial activity of mastic water extract, as well as that of its major constituents, was examined against Escherichia coli, Staphylococcus aureus and Candida spp. including ATCC wild clinical and food-borne strains. Linalool and α-terpineol were found to be the most potent antimicrobial constituents. Finally the stability of mastic water at different temperatures was studied, showing no change in the GC-MS profile of the organic extract for a period of 4 months at storage temperatures up to 4 °C. © 2011 Elsevier Ltd. All rights reserved.
Keywords: 2 methyl 3 buten 2 ol; alpha campholene aldehyde; alpha phellandrenol; Anti-microbial activity; antibacterial activity; antifungal activity; article; Bacteria; bacterial strain; beta phellandrenol; borneol; Candida; Candida albicans; Candida tropicalis; carveol; chemical composition; controlled study; Distillation; enantiomer; Enantiomeric ratio; Enantiomers; Escherichia coli; Essential oils; fenchyl alcohol; gas chromatography; GC-MS analysis; lauryl alcohol; Linalool; mass fragmentography; mass spectrometry; Mastic water; minimum inhibitory concentration; pinanediol; pinocarvone; Pistacia lentiscus; Resins; Solvent extraction; Staphylococcus aureus; terpenoid derivative; terpineol; thermostability; unclassified drug; verbenone; water; XAD4 resin